Double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously generating oxygen in chlorine salt system
Through the double-membrane three-chamber electrolysis method and the titanium mesh/titanium porous Pb-Mn-Co-ZrOx composite electrode, the anode corrosion and environmental pollution problems are solved, the manganese electrolytic efficiency and purity are improved, and the production and environmental protection of high-purity manganese are achieved. .
Patent Information
- Application Number
- CN202411381865.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the process of preparing high-purity manganese with existing metal manganese electrolysis, the anode is easily corroded, the tank voltage is high, the electrolytic efficiency is low, and the environmental pollution is serious.
Using the double-membrane three-chamber electrolysis method, the electrolytic cell is separated into a cathode chamber, an intermediate chamber and anode chamber. An anion exchange membrane and cation exchange membrane are used, oxygen is precipitated on the anode, high-purity manganese is deposited on the cathode, and titanium mesh/titanium porous Pb is used. -Mn-Co-ZrOx composite electrode and purified metal ion impurity removal device to reduce chlorine gas generation and environmental pollution.
The production of high-purity manganese has been achieved, the electrolytic efficiency is improved, the tank voltage is reduced, and the environmental pollution is reduced. The purity of manganese sheet reaches 99.99%-99.999%, and the intermediate chamber hydrochloric acid is recovered for acid-leaved manganese ore.
Abstract
Description
Technical Field
[0001] The invention relates to a double-membrane three-chamber electrolysis method for extracting high-purity manganese from a chloride salt system and simultaneously generating oxygen, belonging to the technical field of hydrometallurgy. Background Art
[0002] The electrodeposition of metallic manganese is mainly based on the sulfuric acid system. However, in the sulfate system, in order to regulate the structure and morphology of manganese, improve the quality of manganese, and stabilize the cathode solution, substances such as SO2 or SeO2 need to be added to the sulfate system. Therefore, the manganese produced by the sulfate medium contains sulfur (0.002% to 0.1%) and selenium, which makes the sulfuric acid system unsuitable for the production of high-purity manganese, while the chloride system can achieve electrolysis of manganese without additives under low temperature conditions. However, the chlorine gas produced at the anode during the electrolysis of manganese in the chloride system limits its application. A large amount of toxic Cl2 is produced from the anode and quickly enters the subsequent reaction, thereby generating hypochlorous acid and hypochlorite ions. The traditional method of inhibiting the chlorine evolution reaction is mostly to synthesize various catalytic coatings on the anode that promote the oxygen evolution reaction. However, these coatings use relatively expensive chemical elements (such as platinum, iridium, etc.), which means that the cost of large-scale promotion will be very high. At the same time, the Cl produced at the anode - And hydrochloric acid will obviously corrode anode materials and other equipment, and damage the environment.
[0003] Therefore, developing new manganese electrolysis methods and realizing manganese electrolysis in a chloride salt system without chlorine gas precipitation at the anode is an important direction for the development of the high-purity manganese industry. Summary of the invention
[0004] Aiming at the problems of easy corrosion of anode, high cell voltage and low electrolysis efficiency in the existing preparation of high-purity manganese by electrolysis of metallic manganese, the present invention proposes a double-membrane three-chamber electrolysis method for extracting high-purity manganese by a chloride system and producing oxygen at the same time. The present invention adopts an anion exchange membrane and a cation exchange membrane to separate an electrolytic cell into a cathode chamber, an intermediate chamber and an anode chamber to form a double-membrane three-chamber electrolytic cell. Electrolysis is carried out in the double-membrane three-chamber electrolytic cell, oxygen is precipitated on the anode and high-purity manganese is deposited on the cathode. Compared with the traditional manganese electrolytic cell, the method of the present invention can obtain high-purity manganese sheets, has high current efficiency and low cell voltage during the electrolysis process, and reduces environmental pollution.
[0005] A double-membrane three-chamber electrolysis method for extracting high-purity manganese in a chloride salt system and simultaneously producing oxygen, the specific steps are as follows:
[0006] The electrolytic cell is divided into a cathode chamber, an intermediate chamber, and an anode chamber by an anion exchange membrane and a cation exchange membrane to form a double-membrane three-chamber electrolytic cell. The electrolyte in the cathode chamber is MnCl2-NH4Cl-NH3·H2O solution, the electrolyte in the intermediate chamber is HCl-KCl solution, and the electrolyte in the anode chamber is H2SO4-(NH4)2SO4-Fe 3+ -Co 2+The solution, the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a stainless steel plate, the cation exchange membrane is a polyethylene / polystyrene cation exchange membrane, a perfluorosulfonic acid type cation exchange membrane or a polyvinylidene fluoride cation exchange membrane, and the anion exchange membrane is an imidazolyl polyetheretherketone anion exchange membrane, a quaternized polyvinyl chloride homogeneous anion exchange membrane or a polyphenylene ether anion exchange membrane;
[0007] Electrolysis is performed in a double-membrane three-chamber electrolytic cell, with oxygen being released on the anode and high-purity manganese being deposited on the cathode.
[0008] Preferably, the electrolyte temperature in the electrolytic cell is 0-20°C, and the anode current density is 400-1200A / m 2 , cathode current density is 200~600A / m 2 The electrolysis time is 12 to 36 hours.
[0009] Preferably, the MnCl2-NH4Cl-NH3·H2O solution contains 100-200 g / L MnCl2, 100-200 g / L NH4Cl and 10-100 ml / L NH3·H2O, and the pH value of the MnCl2-NH4Cl-NH3·H2O solution is 6.0-9.0; the HCl-KCl solution contains 5-15 wt.% HCl and 1-10 wt.% KCl; the H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 20-100 g / L H2SO4, 100-200 g / L (NH4)2SO4, 1-10 g / L Fe 3+ and 0.1~1g / L Co 2+ .
[0010] Preferably, the titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode includes, from the inside to the outside, a titanium mesh / titanium porous base, a Ta-Ti-NbOx intermediate layer, and a Pb-Mn-Co-ZrOx active layer.
[0011] More preferably, in the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb as 100%, Ta accounts for 40-80%, Ti accounts for 15-40%, and Nb accounts for 5-20%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr as 100%, Pb accounts for 50-70%, Mn accounts for 20-30%, Co accounts for 5-10%, and Zr accounts for 5-10%.
[0012] Preferably, the titanium mesh has a mesh length of 6 to 20 mm in the long axis, 2 to 8 mm in the short axis, and a cross-sectional thickness of 1 to 6 mm; the pore size of the titanium porous base is 30 to 200 μm, and the pore depth is 10 to 100 μm; the thickness of the Ta-Ti-NbOx intermediate layer is 1 to 10 μm, and the thickness of the Pb-Mn-Co-ZrOx active layer is 100 to 2000 μm.
[0013] Preferably, the preparation method of the titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode comprises the following steps:
[0014] (a) Pretreatment of titanium mesh or titanium porous substrate: the titanium mesh or titanium porous substrate plate is subjected to coarse sandblasting treatment and then heat-treated at a temperature of 400-600° C. for leveling, placed in a sodium hydroxide solution with a mass concentration of 10-20%, degreased at a temperature of 60-80° C. for 10-30 min, then washed with hot water and placed in an oxalic acid solution with a mass concentration of 5-20%, activated at a temperature of 80-95° C. for 1-2 h, washed with deionized water and dried to obtain a pretreated titanium mesh or pretreated titanium porous substrate;
[0015] (b) Preparation of titanium mesh / titanium porous-based Ta-Ti-NbOx intermediate layer: uniformly coating the surface of the pretreated titanium mesh or the pretreated titanium porous substrate with a Ta-Ti-NbOx precursor liquid, drying at a temperature of 80 to 100°C, and sintering at a temperature of 400 to 700°C for 5 to 10 minutes, repeating the coating of the Ta-Ti-NbOx precursor liquid and the sintering process for 1 to 5 times, and then sintering at 400 to 600°C for 0.5 to 1.5 hours to obtain a titanium mesh-based Ta-Ti-NbOx intermediate layer or a titanium porous-based Ta-Ti-NbOx intermediate layer, and superimposing and welding the titanium mesh-based Ta-Ti-NbOx intermediate layer and the titanium porous-based Ta-Ti-NbOx intermediate layer to obtain a titanium mesh / titanium porous-based Ta-Ti-NbOx intermediate layer;
[0016] (c) Preparation of titanium mesh / titanium porous Pb-Mn-Co-ZrOx composite electrode: The titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer was used as the anode and the titanium mesh was used as the cathode. In a nitrate solution system, the temperature was 80-100°C and the current density was 1-5 A / dm 2 The electrodeposition was stirred for 1 to 5 hours and then washed with deionized water to obtain a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode.
[0017] More preferably, the method for preparing the Ta-Ti-NbOx precursor liquid in step (b) is as follows: dissolving tantalum n-butoxide, butyl titanate and niobium chloride in an isopropanol-n-butanol mixed solvent, and stirring with ultrasound and magnetic force at a temperature of 40 to 60° C. for 1 to 2 hours to obtain a Ta-Ti-NbOx precursor liquid.
[0018] More preferably, the content of tantalum in the Ta-Ti-NbOx precursor liquid is 0.4-0.8 mol / L, the content of titanium is 0.15-0.4 mol / L, the content of niobium is 0.05-0.2 mol / L, and the volume ratio of isopropanol to n-butanol is 1-2:1-2.
[0019] More preferably, the nitrate solution system in step (c) contains 200-300 g / L Pb(NO3)2, 10-100 g / L Mn(NO3)2, 10-40 g / L Co(NO3)2, and 20-60 g / L Zr(NO3)3.
[0020] Preferably, the MnCl2-NH4Cl-NH3·H2O solution is added to the cathode chamber after being purified and impurities removed by a metal ion purification and impurity removal device, wherein the metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles.
[0021] More preferably, the particle size of the metal ion adsorption resin particles is 0.1-1.0 mm, and the particle size of the C / MnO2 nanocomposite particles is 20-160 nm; based on the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles as 100%, the metal ion adsorption resin particles account for 40-60%; based on the mass of the C / MnO2 nanocomposite particles as 100%, nano-C accounts for 40-60%.
[0022] Preferably, the metal ion adsorption resin is 732 ion exchange resin, Amberlite IR120 or Lewatit=MDS TP220.
[0023] Preferably, the preparation method of the C / MnO2 nanocomposite particles is:
[0024] The nanocarbon is added to a sodium nitrate solution, stirred and activated at a temperature of 70-90°C for 1-3 hours, and the solid-liquid is separated. The solid is vacuum dried and then added to a MnCl2 solution, stirred and modified at a temperature of 20-40°C for 12-24 hours, and the solid-liquid is separated. The solid and liquid are washed with deionized water and then added to a NaOH solution, stirred and reacted at a temperature of 20-50°C for 1-3 hours, and the solid-liquid is separated. The solid and liquid are washed with deionized water and then placed in an air atmosphere and calcined at a temperature of 250-500°C for 3-5 hours to obtain C / MnO2 nanocomposite particles.
[0025] Preferably, the concentration of the sodium nitrate solution is 4-8 mol / L, the concentration of the MnCl2 solution is 0.1-0.3 mol / L, and the concentration of the NaOH solution is 0.1-0.3 mol / L.
[0026] The beneficial effects of the present invention are:
[0027] (1) The double-membrane three-chamber electrolysis method of the present invention for extracting high-purity manganese from a chloride salt system and producing oxygen simultaneously can obtain high-purity manganese flakes with a purity of 99.99% to 99.999%, does not produce chlorine, and reduces environmental pollution;
[0028] (2) In the double-membrane three-chamber chloride system electrolytic cell of the present invention, the hydrogen ions continuously generated by the oxygen evolution reaction in the anode will move to the electrolyte in the middle chamber, and due to the restriction of the anion exchange membrane in the cathode chamber, the electrolyte in the middle chamber can be continuously enriched with hydrogen ions; and after electrolysis, the hydrochloric acid in the middle chamber can be recovered for acid leaching of manganese ore, etc.;
[0029] (3) The titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode of the present invention adopts a double-based titanium mesh plate, which can increase the specific surface area of the surface active layer and significantly reduce the oxygen evolution potential of the anode; it has strong electrocatalytic activity, good oxygen evolution and chlorine inhibition catalytic activity, strong corrosion resistance, and reduces the cell voltage;
[0030] (4) The present invention is provided with a metal ion purification and impurity removal device connected to the cathode chamber, and the metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nano-composite particles, so that it has a good ability to selectively purify impure metal ions, and the introduction of MnO2 does not conflict with the purification of manganese electrolyte, so that the purity of the cathode manganese chloride electrolyte reaches 99.99% to 99.999%. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0032] Summary of the Invention
[0033] A double-membrane three-chamber electrolysis method for extracting high-purity manganese in a chloride salt system and simultaneously producing oxygen, the specific steps are as follows:
[0034] The electrolytic cell is divided into a cathode chamber, an intermediate chamber, and an anode chamber by an anion exchange membrane and a cation exchange membrane to form a double-membrane three-chamber electrolytic cell. The electrolyte in the cathode chamber is MnCl2-NH4Cl-NH3·H2O solution, the electrolyte in the intermediate chamber is HCl-KCl solution, and the electrolyte in the anode chamber is H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution, the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a stainless steel plate, the cation exchange membrane is a polyethylene / polystyrene cation exchange membrane, a perfluorosulfonic acid type cation exchange membrane or a polyvinylidene fluoride cation exchange membrane, and the anion exchange membrane is an imidazolyl polyetheretherketone anion exchange membrane, a quaternized polyvinyl chloride homogeneous anion exchange membrane or a polyphenylene ether anion exchange membrane;
[0035] Electrolysis is performed in a double-membrane three-chamber electrolytic cell, oxygen is precipitated on the anode, and high-purity manganese is deposited on the cathode; the electrolyte temperature in the electrolytic cell is 0-20°C, and the anode current density is 400-1200A / m 2 , cathode current density is 200~600A / m 2 , electrolysis time is 12 to 36 hours;
[0036] The MnCl2-NH4Cl-NH3·H2O solution contains 100-200 g / L MnCl2, 100-200 g / L NH4Cl and 10-100 ml / L NH3·H2O, and the pH value of the MnCl2-NH4Cl-NH3·H2O solution is 6.0-9.0; the HCl-KCl solution contains 5-15 wt.% HCl and 1-10 wt.% KCl; the H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 20-100 g / L H2SO4, 100-200 g / L (NH4)2SO4, 1-10 g / L Fe 3+ and 0.1~1g / L Co 2+ ;
[0037] The titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode includes a titanium mesh / titanium porous base, a Ta-Ti-NbOx intermediate layer, and a Pb-Mn-Co-ZrOx active layer from the inside to the outside;
[0038] In the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb as 100%, Ta accounts for 40-80%, Ti accounts for 15-40%, and Nb accounts for 5-20%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr as 100%, Pb accounts for 50-70%, Mn accounts for 20-30%, Co accounts for 5-10%, and Zr accounts for 5-10%;
[0039] The titanium mesh has a mesh long axis of 6 to 20 mm, a short axis of 2 to 8 mm, and a cross-sectional thickness of 1 to 6 mm; the pore size of the titanium porous base is 30 to 200 μm, and the pore depth is 10 to 100 μm; the thickness of the Ta-Ti-NbOx intermediate layer is 1 to 10 μm, and the thickness of the Pb-Mn-Co-ZrOx active layer is 100 to 2000 μm;
[0040] The preparation method of the titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode comprises the following steps:
[0041] (a) Pretreatment of titanium mesh or titanium porous substrate: the titanium mesh or titanium porous substrate plate is subjected to coarse sandblasting treatment and then heat-treated at a temperature of 400-600° C. for leveling, placed in a sodium hydroxide solution with a mass concentration of 10-20%, degreased at a temperature of 60-80° C. for 10-30 min, then washed with hot water and placed in an oxalic acid solution with a mass concentration of 5-20%, activated at a temperature of 80-95° C. for 1-2 h, washed with deionized water and dried to obtain a pretreated titanium mesh or pretreated titanium porous substrate;
[0042] (b) Preparation of titanium mesh / titanium porous-based Ta-Ti-NbOx interlayer: uniformly coating the surface of the pretreated titanium mesh or pretreated titanium porous substrate with a Ta-Ti-NbOx precursor liquid, drying at a temperature of 80 to 100° C., and sintering at a temperature of 400 to 700° C. for 5 to 10 min, repeating the coating of the Ta-Ti-NbOx precursor liquid and the sintering process for 1 to 5 times, and then sintering at 400 to 600° C. for 0.5 to 1.5 h to obtain a titanium mesh-based Ta-Ti-NbOx interlayer or a titanium porous-based Ta-Ti-NbOx interlayer, a titanium mesh-based Ta-Ti-NbOx interlayer, and a titanium porous-based Ta-Ti-NbOx interlayer. bOx intermediate layers are stacked and welded to obtain a titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer; the preparation method of the Ta-Ti-NbOx precursor liquid is as follows: tantalum n-butoxide, butyl titanate and niobium chloride are dissolved in an isopropanol-n-butanol mixed solvent, and ultrasonic and magnetic stirring are performed at a temperature of 40-60°C for 1-2 hours to obtain a Ta-Ti-NbOx precursor liquid; the content of tantalum in the Ta-Ti-NbOx precursor liquid is 0.4-0.8 mol / L, the content of titanium is 0.15-0.4 mol / L, the content of niobium is 0.05-0.2 mol / L, and the volume ratio of isopropanol to n-butanol is 1-2:1-2;
[0043] (c) Preparation of titanium mesh / titanium porous Pb-Mn-Co-ZrOx composite electrode: The titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer was used as the anode and the titanium mesh was used as the cathode. In a nitrate solution system, the temperature was 80-100°C and the current density was 1-5 A / dm 2 Stirring and electro-depositing for 1 to 5 hours, washing with deionized water and hot water to obtain a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode; the nitrate solution system contains 200 to 300 g / L Pb(NO3)2, 10 to 100 g / L Mn(NO3)2, 10 to 40 g / L Co(NO3)2, and 20 to 60 g / L Zr(NO3)3;
[0044] The MnCl2-NH4Cl-NH3·H2O solution is purified and impurities are removed by a metal ion purification and impurity removal device and then added to the cathode chamber. The metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles. The particle size of the metal ion adsorption resin particles is 0.1-1.0 mm, and the particle size of the C / MnO2 nanocomposite particles is 20-160 nm. Based on the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles as 100%, the metal ion adsorption resin particles account for 40-60%; based on the mass of the C / MnO2 nanocomposite particles as 100%, nano C accounts for 40-60%; the metal ion adsorption resin is 732 ion exchange resin, Amberlite IR120 or MDS TP220;
[0045] The preparation method of the C / MnO2 nanocomposite particles:
[0046] The nanocarbon is added to a sodium nitrate solution with a concentration of 4 to 8 mol / L, and activated at a temperature of 70 to 90°C for 1 to 3 hours with stirring, and the solid is separated from the liquid. After vacuum drying, the solid is added to a MnCl2 solution with a concentration of 0.1 to 0.3 mol / L, and modified at a temperature of 20 to 40°C with stirring for 12 to 24 hours. The solid is separated from the liquid, and the solid and liquid are washed with deionized water and added to a NaOH solution with a concentration of 0.1 to 0.3 mol / L, and reacted at a temperature of 20 to 50°C with stirring for 1 to 3 hours. The solid is separated from the liquid, and the solid and liquid are washed with deionized water and then placed in an air atmosphere at a temperature of 250 to 500°C for calcination for 3 to 5 hours to obtain C / MnO2 nanocomposite particles.
[0047] Example 1: A double-membrane three-chamber electrolysis method for extracting high-purity manganese in a chloride system and simultaneously producing oxygen, the specific steps are as follows:
[0048] (1) An anion exchange membrane and a cation exchange membrane are used to separate the electrolytic cell into a cathode chamber, an intermediate chamber, and an anode chamber to form a double-membrane three-chamber electrolytic cell, and a cathode and an anode are placed in the cathode chamber and the anode chamber respectively; the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a 316L stainless steel plate, the cation exchange membrane is a polyethylene / polystyrene cation exchange membrane, and the anion exchange membrane is an imidazole polyetheretherketone anion exchange membrane;
[0049] The titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode includes titanium mesh / titanium porous base, Ta-Ti-NbOx intermediate layer, and Pb-Mn-Co-ZrOx active layer from the inside to the outside; the titanium mesh (TA1 alloy) has a mesh long axis of 6 mm, a short axis of 2 mm, and a cross-sectional thickness of 1 mm; the pore size of the titanium porous base is 30 μm and the pore depth is 10 μm; the thickness of the Ta-Ti-NbOx intermediate layer is 1 μm, and the Pb -Mn-Co-ZrOx active layer thickness is 100 μm; in the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb as 100%, Ta accounts for 40%, Ti accounts for 40%, and Nb accounts for 20%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr as 100%, Pb accounts for 50%, Mn accounts for 30%, Co accounts for 10%, and Zr accounts for 10%;
[0050] The preparation method of the titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode comprises the following steps:
[0051] (a) Pretreatment of titanium mesh or titanium porous substrate: the titanium mesh or titanium porous substrate plate is subjected to coarse sandblasting treatment, heat treatment and leveling at a temperature of 400°C, placed in a sodium hydroxide solution with a mass concentration of 10%, deoiled at a temperature of 60°C for 10 minutes, then washed with hot water and placed in a 5% oxalic acid solution, activated at a temperature of 80°C for 1 hour, washed with deionized water and dried to obtain a pretreated titanium mesh or pretreated titanium porous substrate;
[0052] (b) Preparation of titanium mesh / titanium porous-based Ta-Ti-NbOx interlayer: The Ta-Ti-NbOx precursor liquid was uniformly coated on the surface of the pretreated titanium mesh or pretreated titanium porous substrate, dried at 80°C and sintered at 400°C for 5 min, the coating of the Ta-Ti-NbOx precursor liquid and the sintering process were repeated twice, and then sintered at 400°C for 0.5 h to obtain a titanium mesh-based Ta-Ti-NbOx interlayer or a titanium porous-based Ta-Ti-NbOx interlayer, a titanium mesh-based Ta-Ti-NbOx interlayer and a titanium porous-based Ta-Ti-NbOx interlayer. bOx intermediate layers are stacked and welded to obtain a titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer; the preparation method of the Ta-Ti-NbOx precursor liquid is as follows: tantalum n-butoxide, butyl titanate and niobium chloride are dissolved in an isopropanol-n-butanol mixed solvent, and ultrasonic and magnetic stirring are performed at a temperature of 40°C for 1 hour to obtain a Ta-Ti-NbOx precursor liquid; the content of tantalum in the Ta-Ti-NbOx precursor liquid is 0.4 mol / L, the content of titanium is 0.15 mol / L, the content of niobium is 0.05 mol / L, and the volume ratio of isopropanol to n-butanol is 1:2;
[0053] (c) Preparation of titanium mesh / titanium porous Pb-Mn-Co-ZrOx composite electrode: The titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer was used as the anode and the titanium mesh was used as the cathode. The electrode was charged in a nitrate solution at a temperature of 80 °C and a current density of 1 A / dm 2 Stir and electro-deposit for 1 hour, and wash with deionized water to obtain a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode; the nitrate solution system contains 200g / L Pb(NO3)2, 10g / L Mn(NO3)2, 10g / L Co(NO3)2, and 20g / L Zr(NO3)3;
[0054] (2) using a peristaltic pump to pass the MnCl2-NH4Cl-NH3·H2O stock solution into a metal ion purification and impurity removal device for circulation purification 7 times at a speed of 1 ml / L to obtain a cathode purification solution (MnCl2-NH4Cl-NH3·H2O solution), and the cathode purification solution is passed into the cathode chamber as the electrolyte of the cathode chamber, and the pH value of the electrolyte in the cathode chamber is controlled to be 6.0; the MnCl2-NH4Cl-NH3·H2O solution contains 100 g / L MnCl2, 100 g / L NH4Cl and 10 ml / L NH3·H2O;
[0055] The metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles; the particle size of the metal ion adsorption resin particles is 0.1 mm, and the particle size of the C / MnO2 nanocomposite particles is 20 nm; based on the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles being 100%, the metal ion adsorption resin particles account for 40%; based on the mass of the C / MnO2 nanocomposite particles being 100%, nano C accounts for 60%; the metal ion adsorption resin is 732 ion exchange resin;
[0056] The preparation method of the C / MnO2 nanocomposite particles:
[0057] The nanocarbon was added to a sodium nitrate solution with a concentration of 4 mol / L, and activated by stirring at a temperature of 70°C for 1 hour, and the solid-liquid separation was performed. The solid was washed with a deionized water-acetic acid mixed solution (the volume ratio of deionized water and acetic acid was 1:1). The solid was vacuum dried at a temperature of 50°C for 2 hours and then added to a MnCl2 solution with a concentration of 0.1 mol / L, and stirred and modified at a temperature of 40°C for 12 hours, and the solid-liquid separation was performed. The solid and liquid were washed with deionized water and then added to a NaOH solution with a concentration of 0.1 mol / L, and stirred and reacted at a temperature of 40°C for 1 hour, and the solid-liquid separation was performed. The solid and liquid were washed with deionized water and then placed in an air atmosphere at a temperature of 250°C for calcination for 3 hours to obtain C / MnO2 nanocomposite particles.
[0058] (3) HCl-KCl solution is added to the intermediate chamber as the intermediate chamber electrolyte, and H2SO4-(NH4)2SO4-Fe is added to the anode chamber. 3+ -Co 2+ The solution is used as the electrolyte in the anode chamber; the HCl-KCl solution contains 5wt.% HCl and 1wt.% KCl; H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 20g / L H2SO4, 100g / L (NH4)2SO4, 1g / L Fe 3+ and 0.1g / LCo 2+ ;
[0059] (4) Control the electrolyte temperature in the electrolytic cell to 0°C and the anode current density to 400A / m 2 , cathode current density is 200A / m 2 , the electrolysis time is 12h, oxygen is precipitated on the anode, and high-purity manganese is deposited on the cathode;
[0060] During the electrolysis process of this embodiment, no chlorine gas is volatilized from the anode, and only high-purity oxygen is precipitated. Under the same conditions, compared with the traditional anode (Pb-0.5% Ag-0.07% Ca), the cell voltage is reduced by 0.1V, and the purity of the manganese sheet on the cathode is 99.99%.
[0061] Example 2: A double-membrane three-chamber electrolysis method for extracting high-purity manganese in a chloride system and simultaneously producing oxygen, the specific steps are as follows:
[0062] (1) An anion exchange membrane and a cation exchange membrane are used to separate the electrolytic cell into a cathode chamber, an intermediate chamber, and an anode chamber to form a double-membrane three-chamber electrolytic cell, and a cathode and an anode are placed in the cathode chamber and the anode chamber respectively; the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a 317L molybdenum-containing stainless steel medium and thick plate, the cation exchange membrane is a polyvinylidene fluoride cation exchange membrane, and the anion exchange membrane is a polyphenylene ether anion exchange membrane;
[0063] The titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode includes titanium mesh / titanium porous base, Ta-Ti-NbOx intermediate layer, and Pb-Mn-Co-ZrOx active layer from the inside to the outside; the titanium mesh (TA1 alloy) has a mesh long axis of 20 mm, a short axis of 8 mm, and a cross-sectional thickness of 6 mm; the pore size of the titanium porous base is 200 μm and the pore depth is 100 μm; the thickness of the Ta-Ti-NbOx intermediate layer is 10 μm , the thickness of the Pb-Mn-Co-ZrOx active layer is 2000 μm; in the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb as 100%, Ta accounts for 80%, Ti accounts for 15%, and Nb accounts for 5%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr as 100%, Pb accounts for 70%, Mn accounts for 20%, Co accounts for 5%, and Zr accounts for 5%;
[0064] The preparation method of the titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode comprises the following steps:
[0065] (a) Pretreatment of titanium mesh or titanium porous substrate: the titanium mesh or titanium porous substrate plate is subjected to coarse sandblasting treatment, heat treatment at a temperature of 600°C for leveling, placed in a sodium hydroxide solution with a mass concentration of 20%, degreased at a temperature of 80°C for 30 minutes, then washed with hot water and placed in a 20% oxalic acid solution, activated at a temperature of 95°C for 2 hours, washed with deionized water and dried to obtain a pretreated titanium mesh or pretreated titanium porous substrate;
[0066] (b) Preparation of titanium mesh / titanium porous-based Ta-Ti-NbOx interlayer: The Ta-Ti-NbOx precursor liquid was uniformly coated on the surface of the pretreated titanium mesh or pretreated titanium porous substrate, dried at 100°C, and then sintered at 600°C for 10 min. The coating of the Ta-Ti-NbOx precursor liquid and the sintering process were repeated 5 times, and then sintered at 600°C for 1.5 h to obtain a titanium mesh-based Ta-Ti-NbOx interlayer or a titanium porous-based Ta-Ti-NbOx interlayer. The titanium mesh-based Ta-Ti-NbOx interlayer and the titanium porous-based Ta-Ti -NbOx intermediate layers are stacked and welded to obtain a titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer; the preparation method of the Ta-Ti-NbOx precursor liquid is as follows: tantalum n-butoxide, butyl titanate and niobium chloride are dissolved in an isopropanol-n-butanol mixed solvent, and ultrasonic and magnetic stirring are performed at a temperature of 60°C for 2 hours to obtain a Ta-Ti-NbOx precursor liquid; the content of tantalum in the Ta-Ti-NbOx precursor liquid is 0.8 mol / L, the content of titanium is 0.4 mol / L, the content of niobium is 0.2 mol / L, and the volume ratio of isopropanol to n-butanol is 2:1;
[0067] (c) Preparation of titanium mesh / titanium porous Pb-Mn-Co-ZrOx composite electrode: The titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer was used as the anode and the titanium mesh was used as the cathode. The electrode was charged in a nitrate solution at a temperature of 100 °C and a current density of 5 A / dm 2 Stir and electrodeposit for 5 hours, and wash with deionized water to obtain a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode; the nitrate solution system contains 300g / L Pb(NO3)2, 100g / L Mn(NO3)2, 40g / L Co(NO3)2, and 60g / L Zr(NO3)3;
[0068] (2) using a peristaltic pump to pass the MnCl2-NH4Cl-NH3·H2O stock solution into a metal ion purification and impurity removal device for circulation purification 10 times at a speed of 5 ml / L to obtain a cathode purification solution (MnCl2-NH4Cl-NH3·H2O solution), the cathode purification solution is passed into the cathode chamber as the electrolyte of the cathode chamber, and the pH value of the electrolyte in the cathode chamber is controlled to be 9.0; the MnCl2-NH4Cl-NH3·H2O solution contains 200 g / L MnCl2, 200 g / L NH4Cl and 100 ml / L NH3·H2O;
[0069] The metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles; the particle size of the metal ion adsorption resin particles is 1.0 mm, and the particle size of the C / MnO2 nanocomposite particles is 160 nm; based on the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles being 100%, the metal ion adsorption resin particles account for 60%; based on the mass of the C / MnO2 nanocomposite particles being 100%, nano C accounts for 40%; the metal ion adsorption resin is Amberlite IR120;
[0070] The preparation method of the C / MnO2 nanocomposite particles:
[0071] The nanocarbon was added to a sodium nitrate solution with a concentration of 8 mol / L, and activated by stirring at a temperature of 90°C for 3 hours, and the solid-liquid separation was performed. The solid was washed with a deionized water-acetic acid mixed solution (the volume ratio of deionized water and acetic acid was 1:1). The solid was vacuum dried at a temperature of 70°C for 5 hours and then added to a MnCl2 solution with a concentration of 0.3 mol / L, and stirred and modified at a temperature of 20°C for 24 hours, and the solid-liquid separation was performed. The solid and liquid were washed with deionized water and then added to a NaOH solution with a concentration of 0.3 mol / L, and stirred and reacted at a temperature of 50°C for 3 hours, and the solid-liquid separation was performed. The solid and liquid were washed with deionized water and then placed in an air atmosphere and calcined at a temperature of 500°C for 5 hours to obtain C / MnO2 nanocomposite particles.
[0072] (3) HCl-KCl solution is added to the intermediate chamber as the intermediate chamber electrolyte, and H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution is used as the electrolyte in the anode chamber; the HCl-KCl solution contains 15wt.% HCl and 10wt.% KCl; H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 100g / L H2SO4, 200g / L (NH4)2SO4, 10g / L Fe 3+ and 1g / LCo 2 + ;
[0073] (4) Control the electrolyte temperature in the electrolytic cell to 40°C and the anode current density to 1200A / m 2 , cathode current density is 600A / m 2 , the electrolysis time is 36h, oxygen is precipitated on the anode, and high-purity manganese is deposited on the cathode;
[0074] During the electrolysis process of this embodiment, no chlorine gas is volatilized at the anode, and only high-purity oxygen is precipitated. Under the same conditions, compared with the traditional anode (Pb-0.5% Ag-0.07% Ca), the cell voltage is reduced by 0.3V, and the purity of the manganese sheet on the cathode is 99.995%.
[0075] Example 3: A double-membrane three-chamber electrolysis method for extracting high-purity manganese in a chloride system and simultaneously producing oxygen, the specific steps are as follows:
[0076] (1) An anion exchange membrane and a cation exchange membrane are used to separate the electrolytic cell into a cathode chamber, an intermediate chamber, and an anode chamber to form a double-membrane three-chamber electrolytic cell, and a cathode and an anode are placed in the cathode chamber and the anode chamber respectively; the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a S31703 stainless steel plate, the cation exchange membrane is a perfluorosulfonic acid type cation exchange membrane, and the anion exchange membrane is a quaternary ammonium polyvinyl chloride homogeneous anion exchange membrane;
[0077] The titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode includes titanium mesh / titanium porous base, Ta-Ti-NbOx intermediate layer, and Pb-Mn-Co-ZrOx active layer from the inside to the outside. The titanium mesh (TA1 alloy) has a mesh long axis of 15 mm, a short axis of 5 mm, and a cross-sectional thickness of 3 mm. The pore size of the titanium porous base is 100 μm and the pore depth is 50 μm. The thickness of the Ta-Ti-NbOx intermediate layer is 5 μm, The thickness of the Pb-Mn-Co-ZrOx active layer is 1000 μm; in the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb being 100%, Ta accounts for 60%, Ti accounts for 25%, and Nb accounts for 15%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr being 100%, Pb accounts for 60%, Mn accounts for 25%, Co accounts for 6%, and Zr accounts for 9%;
[0078] The preparation method of the titanium mesh / titanium porous-based Pb-Mn-Co-ZrOx composite electrode comprises the following steps:
[0079] (a) Pretreatment of titanium mesh or titanium porous substrate: The titanium mesh or titanium porous substrate plate is subjected to coarse sandblasting treatment, heat treatment at a temperature of 500°C for leveling, placed in a sodium hydroxide solution with a mass concentration of 15%, degreased at a temperature of 70°C for 20 minutes, then washed with hot water and placed in a 15% oxalic acid solution, activated at a temperature of 85°C for 1.5 hours, washed with deionized water and dried to obtain a pretreated titanium mesh or pretreated titanium porous substrate;
[0080] (b) Preparation of titanium mesh / titanium porous-based Ta-Ti-NbOx interlayer: The Ta-Ti-NbOx precursor liquid was uniformly coated on the surface of the pretreated titanium mesh or pretreated titanium porous substrate, dried at 90°C and sintered at 500°C for 8 min, the coating of the Ta-Ti-NbOx precursor liquid and the sintering process were repeated three times, and then sintered at 500°C for 1 h to obtain a titanium mesh-based Ta-Ti-NbOx interlayer or a titanium porous-based Ta-Ti-NbOx interlayer, a titanium mesh-based Ta-Ti-NbOx interlayer and a titanium porous-based Ta-Ti-Nb Ox intermediate layers are stacked and welded to obtain a titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer; the preparation method of the Ta-Ti-NbOx precursor liquid is as follows: tantalum n-butoxide, butyl titanate and niobium chloride are dissolved in an isopropanol-n-butanol mixed solvent, and ultrasonic and magnetic stirring are performed at a temperature of 50°C for 1.5 hours to obtain a Ta-Ti-NbOx precursor liquid; the content of tantalum in the Ta-Ti-NbOx precursor liquid is 0.6 mol / L, the content of titanium is 0.2 mol / L, the content of niobium is 0.1 mol / L, and the volume ratio of isopropanol to n-butanol is 1:1;
[0081] (c) Preparation of titanium mesh / titanium porous Pb-Mn-Co-ZrOx composite electrode: The titanium mesh / titanium porous Ta-Ti-NbOx intermediate layer was used as the anode and the titanium mesh was used as the cathode. The current density was 3A / dm in a nitrate solution system at a temperature of 90°C. 2 Stir and electro-deposit for 3 hours, and wash with deionized water to obtain a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode; the nitrate solution system contains 250g / L Pb(NO3)2, 60g / L Mn(NO3)2, 20g / L Co(NO3)2, and 40g / L Zr(NO3)3;
[0082] (2) using a peristaltic pump to pass the MnCl2-NH4Cl-NH3·H2O stock solution into a metal ion purification and impurity removal device for eight times at a speed of 3 ml / L to obtain a cathode purification solution (MnCl2-NH4Cl-NH3·H2O solution), the cathode purification solution is passed into the cathode chamber as the electrolyte of the cathode chamber, and the pH value of the electrolyte in the cathode chamber is controlled to be 7.0; the MnCl2-NH4Cl-NH3·H2O solution contains 150 g / L MnCl2, 150 g / L NH4Cl and 50 ml / L NH3·H2O;
[0083] The metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles; the particle size of the metal ion adsorption resin particles is 0.5mm, and the particle size of the C / MnO2 nanocomposite particles is 80nm; based on the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles being 100%, the metal ion adsorption resin particles account for 50%; based on the mass of the C / MnO2 nanocomposite particles being 100%, the nano C accounts for 50%; the metal ion adsorption resin is MDS TP220;
[0084] The preparation method of the C / MnO2 nanocomposite particles:
[0085] The nanocarbon was added to a 6 mol / L sodium nitrate solution, stirred and activated at 80°C for 2 hours, solid-liquid separation was performed, the solid was washed with a deionized water-acetic acid mixed solution (the volume ratio of deionized water and acetic acid was 1:1), the solid was vacuum dried at 60°C for 3 hours, then added to a 0.2 mol / L MnCl2 solution, stirred and modified at 30°C for 18 hours, solid-liquid separation was performed, the solid and liquid were washed with deionized water, then added to a 0.2 mol / L NaOH solution, stirred and reacted at 30°C for 2 hours, solid-liquid separation was performed, the solid and liquid were washed with deionized water, then placed in an air atmosphere and calcined at 350°C for 4 hours to obtain C / MnO2 nanocomposite particles;
[0086] (3) HCl-KCl solution is added to the intermediate chamber as the intermediate chamber electrolyte, and H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution is used as the electrolyte in the anode chamber; the HCl-KCl solution contains 10wt.% HCl and 5wt.% KCl; H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 60g / L H2SO4, 150g / L (NH4)2SO4, 5g / L Fe 3+ and 0.5g / LCo 2+ ;
[0087] (4) The electrolyte temperature in the electrolytic cell is controlled at 5°C and the anode current density is 800A / m 2 , cathode current density is 400A / m 2 , the electrolysis time is 24h, oxygen is precipitated on the anode, and high-purity manganese is deposited on the cathode;
[0088] During the electrolysis process of this embodiment, no chlorine gas is volatilized at the anode, and only high-purity oxygen is precipitated. Under the same conditions, compared with the traditional anode (Pb-0.5% Ag-0.07% Ca), the cell voltage is reduced by 0.5V, and the purity of the manganese sheet on the cathode is 99.999%.
[0089] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A double membrane three-chamber electrolysis method for extracting high-purity manganese from a chloride system and simultaneously producing oxygen, characterized in that: The specific steps are as follows: The electrolytic cell is divided into a cathode chamber, an intermediate chamber, and an anode chamber by an anion exchange membrane and a cation exchange membrane to form a double-membrane three-chamber electrolytic cell. The electrolyte in the cathode chamber is MnCl2-NH4Cl-NH3·H2O solution, the electrolyte in the intermediate chamber is HCl-KCl solution, and the electrolyte in the anode chamber is H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution, the anode is a titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode, the cathode is a stainless steel plate, the cation exchange membrane is a polyethylene / polystyrene cation exchange membrane, a perfluorosulfonic acid type cation exchange membrane or a polyvinylidene fluoride cation exchange membrane, and the anion exchange membrane is an imidazolyl polyetheretherketone anion exchange membrane, a quaternized polyvinyl chloride homogeneous anion exchange membrane or a polyphenylene ether anion exchange membrane; Electrolysis is performed in a double-membrane three-chamber electrolytic cell, with oxygen being released on the anode and high-purity manganese being deposited on the cathode.
2. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 1, characterized in that: The electrolyte temperature in the electrolytic cell is 0-20°C, and the anode current density is 400-1200A / m 2 , cathode current density is 200~600A / m 2 The electrolysis time is 12 to 36 hours.
3. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 1, characterized in that: The MnCl2-NH4Cl-NH3·H2O solution contains 100-200 g / L MnCl2, 100-200 g / L NH4Cl and 10-100 ml / L NH3·H2O, and the pH value of the MnCl2-NH4Cl-NH3·H2O solution is 6.0-9.0; the HCl-KCl solution contains 5-15 wt.% HCl and 1-10 wt.% KCl; the H2SO4-(NH4)2SO4-Fe 3+ -Co 2+ The solution contains 20-100 g / L H2SO4, 100-200 g / L (NH4)2SO4, 1-10 g / L Fe 3+ and 0.1~1g / L Co 2+ .
4. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 1, characterized in that: The titanium mesh / titanium porous base Pb-Mn-Co-ZrOx composite electrode comprises a titanium mesh / titanium porous base, a Ta-Ti-NbOx intermediate layer, and a Pb-Mn-Co-ZrOx active layer in sequence from the inside to the outside.
5. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 4, characterized in that: In the Ta-Ti-NbOx intermediate layer, based on the total molar amount of Ta, Ti and Nb as 100%, Ta accounts for 40-80%, Ti accounts for 15-40%, and Nb accounts for 5-20%; in the Pb-Mn-Co-ZrOx active layer, based on the total molar amount of Pb, Mn, Co and Zr as 100%, Pb accounts for 50-70%, Mn accounts for 20-30%, Co accounts for 5-10%, and Zr accounts for 5-10%.
6. The double-membrane three-chamber electrolysis method for extracting high-purity manganese from a chloride salt system and simultaneously producing oxygen according to claim 4 or 5, characterized in that: The titanium mesh has a mesh long axis of 6 to 20 mm, a short axis of 2 to 8 mm, and a cross-sectional thickness of 1 to 6 mm; the pore size of the titanium porous base is 30 to 200 μm, and the pore depth is 10 to 100 μm; the thickness of the Ta-Ti-NbOx intermediate layer is 1 to 10 μm, and the thickness of the Pb-Mn-Co-ZrOx active layer is 100 to 2000 μm.
7. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 1, characterized in that: The MnCl2-NH4Cl-NH3·H2O solution is added into the cathode chamber after being purified and impurities removed by a metal ion purification and impurity removal device, wherein the metal ion purification and impurity removal device is filled with metal ion adsorption resin particles and C / MnO2 nanocomposite particles.
8. The double-membrane three-chamber electrolysis method for extracting high-purity manganese and simultaneously producing oxygen in a chloride salt system according to claim 7, characterized in that: The particle size of the metal ion adsorption resin particles is 0.1-1.0 mm, and the particle size of the C / MnO2 nanocomposite particles is 20-160 nm; taking the total mass of the metal ion adsorption resin particles and the C / MnO2 nanocomposite particles as 100%, the metal ion adsorption resin particles account for 40-60%; taking the mass of the C / MnO2 nanocomposite particles as 100%, nano-C accounts for 40-60%.
Citation Information
Cited By
Electrolysis device and method for preparing high-purity manganese through manganese chloride electrolysis
CN121110121A
